2012
DOI: 10.1182/blood-2012-01-407395
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection of human macrophages directly induces viperin which inhibits viral production

Abstract: AbstractMacrophages are key target cells for HIV-1. HIV-1BaL induced a subset of interferon-stimulated genes in monocyte-derived macrophages (MDMs), which differed from that in monocyte-derived dendritic cells and CD4 T cells, without inducing any interferons. Inhibition of type I interferon induction was mediated by HIV-1 inhibition of interferon-regulated factor (IRF3) nuclear translocation. In MDMs, viperin was the most up-regulated interferon-stimulated genes, and it signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
209
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(225 citation statements)
references
References 50 publications
12
209
4
Order By: Relevance
“…This result is in agreement with previous reports showing that HIV-1 infection of macrophages neither triggered IRF3 pathways nor induced type-I IFN gene expression (78)(79)(80)(81). Moreover, a recent report showed that mDCs and macrophages fail to induce expression of all known type-I and type-III IFN genes in response to HIV-1 (82).…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagesupporting
confidence: 83%
“…This result is in agreement with previous reports showing that HIV-1 infection of macrophages neither triggered IRF3 pathways nor induced type-I IFN gene expression (78)(79)(80)(81). Moreover, a recent report showed that mDCs and macrophages fail to induce expression of all known type-I and type-III IFN genes in response to HIV-1 (82).…”
Section: Hiv-1-mediated Baff Induction Is Modulated By the Macrophagesupporting
confidence: 83%
“…The consensus from these studies is that viperin likely exerts its activity through different pathways that depend on the particular virus and that it interacts with multiple cellular and viral proteins in the process (19,27,31,33,34). Previous studies, using a truncated version of viperin, recombinantly produced and purified from E. coli, have demonstrated that the enzyme cleaves SAM to form 5Ј-dA (22), which is the hallmark reaction of radical SAM enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is induced by host PRRs, among which nucleic acid sensors are known to play particularly important roles [2]. In contrast to the typical scenario, HIV-1 infection of T-cells and macrophages does not stimulate IRF3 activation and fails to induce IFN expression, but does lead to expression of a subset of ISGs [3][4][5]. However, it has been reported that HIV-1 genomic RNA can induce IFN responses in specific cell culture systems via toll-like receptor 7 and retinoid-acid inducible gene I [6][7][8].…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Is the Cause Ofmentioning
confidence: 99%